Relationship Between Mortality and Seizures After Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis - Lin, Hong-yu; Wei, Qing-qing; Huang, Jian-yi; Pan, Xing-hua; Liang, Ning-chao; Huang, Cai-xia; Long, Teng; Gao, Wen; Shi, Sheng-liang (Frontiers in Neurology, 2022)
Background：The relationship between mortality and seizures after intracerebral hemorrhage (ICH) has not be understood until now. A meta-analysis was performed to assess the effect of post-ICH seizures on mortality among ICH patients. Methods: PubMed and Embase were searched from the establishment of the databases to December 2021 to identify literature that evaluated the relationship between post-ICH seizures and mortality in ICH. Crude odds ratios and adjusted odds ratios with a 95% confidence interval (CI) were pooled using a random-effects model. Results: Thirteen studies involving 245,908 participants were included for analysis eventually. The pooled estimate suggested that post-ICH seizures were not associated with a significant increased mortality in patients with ICH (crude adds ratios 1.35, 95% CI: 0.91–2.00; adjusted adds ratios 1.22, 95% CI: 0.78–1.88). However, the relationship was not consistent in subgroup analysis or robust in sensitivity analysis. Conclusions: This meta-analysis proved that post-ICH seizures were not associated with a significant increased mortality in patients with ICH. However, this result could be influenced by confounding factors and so more high quality research is needed.